Temporomandibular Disorders are Associated with Sociodemographic Factors, Health-Related and Oral Conditions in Adolescents: A Cross-Sectional Study - Ana Luiza Peres Baldiotti; Gabrielle Amaral-Freitas; Rafaela Scariot; Maria Luísa Leandro de Souza Dias; Renata de Castro Martins; Saul Martins Paiva; Fernanda Morais Ferreira (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2022)
Objective: To assess the association between temporomandibular disorder (TMD) with sociodemographic factors, health-related factors, and oral conditions in adolescents. Material and Methods: This cross-sectional study was developed with 89 adolescents between 13 to 18 years. TMD diagnosis was obtained by the Research Diagnostic Criteria for Temporomandibular Disease (RDC/TMD) Axis I. Diagnoses of chronic pain, depression, presence of non-specific physical symptoms, including pain and anxiety, were obtained by the RDC/TMD Axis II. The feeling of happiness was measured by the Subjective Happiness Scale. Socio-economic and demographic characteristics were collected through self-administered questionnaires. Patients were examined for dental caries, dental trauma, malocclusion, and tooth wear. Parents answered a sociodemographic, economic, and general health questionnaire. Data were submitted to descriptive statistics, and a logistic regression model was used to assess the association between TMD and the socio-economic, demographic, health-related, and clinical variables. Results: TMD prevalence was 42%. TMD was associated to skin color (p=0.040), use of medications in the past year (p = 0.020) and previous dental trauma (p=0.030). Also, it tended to be associated with the presence of probable awake bruxism (p=0.053). Conclusion: Sociodemographic factors, health-related factors, and oral conditions play a role in TMD, with nonwhite adolescents, those who had used medications in the past year and/or had previous dental trauma having a greater chance of present this disorder.